A Facile Synthesis of Highly Efficient MXene Supported CoMoS Catalysts for Hydrodesulfurization. Issue 7 (7th June 2022) - Vinoba, Mari; Al‐Sheeha, Hanadi; AlSairafi, Sakeena H.
Abstract: In this study, ammonium tetrathiomolybdate (ATM) and 2D‐layer MXene support were used to prepare more efficient MoS2 catalysts with cobalt promoter for the elimination of sulfur atoms in thiophene. A series of well‐dispersed and highly active MoS2 and Co−Mo−S phase on MXene catalysts were derived by thermal activation of precursors varying promoter cobalt to molybdenum molar ratio up to 0.6. The physicochemical properties of synthesized catalysts were characterized by XRD, TPR, SEM/EDS, XPS, HRTEM, and Raman spectroscopy. The as‐prepared MoS2 /MXene and Co−MoS2 /MXene catalysts were examined for thiophene hydrodesulfurization (HDS) at 300–400 °C. The synergetic effect between Co and few‐layer MoS2 on MXene, enhanced their HDS activity to ∼ 20.6 mmol g −1 h −1 with an excellent turnover frequency of about 55 h −1 achieved on Co−MoS2 /MXene catalysts, which were 8‐fold higher than the conventional CoMoS/alumina catalyst. Co−MoS2 /MXene catalysts produce high butenes selectivity ∼73% at low temperature, whereas, at high‐temperature alkane levels were increased ∼42% in CoMoS phase through hydrogen activation. Hence, the few‐layer MoS2 obtained from ATM and promoter Co intercalated MXene catalysts enhances the rate of C−S bond cleavage in HDS, and the result is scrubbing a large volume of sulfur atoms in clean fuel processes. Abstract : 2D‐Material‐based catalysts with a highly dispersed CoMoS phase between MXene layers were prepared by in‐situ thermal activation. The synergism between CoMoS and MXene increased the thiophene HDS turnover frequency to ∼55 h −1, and also promotes the cobalt‐enhanced HDS rate by 8‐fold when compare to MoS2 /MXene catalysts.